Evaluation of the Effect of Static and Flowing Conditions on the Corrosion Behavior of the Hull of Marine Ships (Journal of Engineering, 2024)
Marine ship hulls' corrosion resistance behavior under static and flowing conditions was investigated. The metal of the hull panels of marine ships was chemically and mechanically examined and analyzed, revealing that carbon steel type DIN 1.0501 C35 is employed in constructing the hull of ships in the port of Basrah in Iraq. A corrosion resistance test for this metal was carried out in laboratory-prepared seawater under static and flowing conditions at a flow rate of 1500 liter/hour and various immersion times (12, 24, 48, 120, 168, 336) hours. The temperature was kept constant at 30°C, and a fixed salt concentration of (3.5% sodium chloride). The corrosion rate of C35 carbon steel was calculated using the weight loss method is an effective method for calculating the corrosion rate of carbon steel. The samples were examined using a scanning electron microscope (SEM) for corrosion analysis. Conclusions from this research indicate that an increase in the flow rate resulted in an elevation of the corrosion rate, doubling the corrosion rate compared to samples under static conditions. The corrosion rate exhibited a significant increase during the first 24 hours, followed by a gradual decrease with increasing immersion time. The corrosion rate increased by 682.9%. The speed of corrosion was fast initially, but the weight loss slowed after 24 hours of immersion. A scanning electron microscope (SEM) examination revealed that the flow environment was aggressive for carbon steel. It was much more severe, and the pits and grooves were more significant than the static condition.